PEMBERDAYAAN GURU DALAM PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA SMP TAHAP LESSON PLAN DALAM SISTIM LSLC - Anselmus Boy Baunsele; Hildegardis Missa; Hironimus Tangi; Yanti Rosinda Tinenti (Jurnal Pengabdian UntukMu NegeRI, 2019)
Abstract This PKM is conducted at Sint Vianney Middle School which is located at JLN. I Gusti Ngurah Rai, Kampung Baru Village, Soe City District, TTS Regency, NTT Province. The resulting target is an increase in the ability of teachers to design learning devices that meet the standards of the learning process, improvement in the ability of teachers to develop assessment instruments for aspects of knowledge (KI 3) that include high order thinking skills (High Order Thingking Skill / HOT), skills (KI 4 ), and optimizing the use of practical tools and materials in schools and the surrounding environment in the process of developing learning tools. Activities that have been carried out to achieve the above PKM targets consist of a lesson plan phase in the Lesson Study Learning Community (LSLC) system, namely:1. Planning the PKM activity schedule with the team leader, members and teachers in the school.2. Seminar on the implementation of the LSLC system, development of learning tools, and assessment instruments that meet the process standards and assessment standards in the 2013 curriculum.3. Lesson plan in the Lesson Study Learning Community (LSLC) system. Keywords: Lesson Plan, LSLC, High Order Thingking Abstrak PKM ini dilakukan di SMPK Sint Vianney yang beralamat di JLN. I Gusti Ngurah Rai, Kelurahan Kampung Baru, Kecamatan Kota Soe Kabupaten TTS, Provinsi NTT. Target yang dihasilkan yakni peningkatan kemampuan guru dalam merancang perangkat pembelajaran yang memenuhi standar proses pembelajaran, peningkatan kemampuan guru dalam mengembangkan instrumen penilaian untuk aspek pengetahuan (KI 3) yang mencakup kemampuan berpikir tingkat tinggi (High order Thingking Skill/HOT), keterampilan (KI 4), dan optimalisasi penggunaan alat dan bahan praktikum di sekolah maupun di lingkungan sekitar dalam proses pengembangan perangkat pembelajaran. Kegiatan yang telah dilakukan untuk mencapai target PKM di atas terdiri dari tahap perencanaan (lesson plan) pada sistim Lesson Study Learning Community (LSLC), yakni: Perencanaan jadwal kegiatan PKM bersama ketua tim, anggota dan guru-guru di sekolah. Seminar tentang pelaksanaan sistem LSLC, pengembangan perangkat pembelajaran, dan instrumen penilaian yang memenuhi standar proses dan standar penilaian dalam kurikulum 2013. Tahap Perencanaan (lesson plan) pada sistim Lesson Study Learning Community (LSLC). Kata Kunci : Lesson Plan, LSLC, High Order Thingking.